Nurses knowledge of managing patients with COVID-19 disease respiratory dysfunction in intensive care unit - Bukartienė, Loreta; Lukianskytė, Rūta; Maksvytytė, Kamilė; Petkutė, Mantė (Slauga. Mokslas ir praktika, 2023)
Summary. Manifestations of the disease in patients with COVID-19 disease are extremely wide, which requires new nursing strategies. To better help a patient with respiratory problems with a COVID-19 disease, you need to focus not only on treatment, but also on nursing. The aim of the research – to determine nurses knowledge of managing patients with COVID-19 disease respiratory dysfunction in intensive care unit. The methods of the research. After analyzing the scientific literature, the quantitative study was prepared – the questionnaire survey consisting of 20 questions. The survey was carried out in November 2022 and the analysis of the survey data was carried out in December 2022. 107 intensive care unit nurses participated in the research. Conclusions. Main results of the empirical research showed, that nurses have quite strong knowledge how to manage respiratory disorders in patients with COVID-19 disease. According to the respondents perceptions, the most effective action is the application of a face mask with reservoir.